Molecular Engineering of Chalcogen‐Embedded Anthanthrenes via peri‐Selective C−H Activation: Fine‐Tuning of Crystal Packing for Organic Field‐Effect Transistors. (8th December 2022) - Liu, Zheng; Han, Weiguo; Lan, Jingbo; Sun, Lingyan; Tang, Junbin; Zhang, Cheng; You, Jingsong
Abstract: Disclosed herein is a RhCl3 ‐catalyzed peri ‐selective C−H/C−H oxidative homo‐coupling of 1‐substituted naphthalenes, which provides a highly efficient and streamlined approach to chalcogen‐embedded anthanthrenes from readily available starting materials. Introducing O, S, and Se into the anthanthrene skeleton leads to gradually increased π–π stacking distances but significantly enhanced π–π overlaps with the growth of the hetero‐atom radius. Moderate π–π distance, overlap area, and intermolecular S−S interactions endow S‐embedded anthanthrene (PTT ) with excellent 2D charge‐transport properties. Moreover, the transformation of p‐type to n‐type S‐embedded anthanthrenes is realized for the first time via the S‐atom oxidation from PTT to PTT‐O4 . In organic field‐effect transistor devices, PTT derivatives exhibit hole transport with mobilities up to 1.1 cm 2 V −1 s −1, while PTT‐O4 shows electron transport with a mobility of 0.022 cm 2 V −1 s −1 . Abstract : RhCl3 ‐catalyzed peri ‐selective C−H/C−H oxidative homo‐coupling of 1‐substituted naphthalenes is developed to access chalcogen‐embedded anthanthrenes. S‐embedded anthanthrene (PTT ) exhibits hole transport with a mobility of 1.1 cm 2 V −1 s −1 . The transformation of p‐type to n‐type semiconductors is realized via the S‐atom oxidation of PTT, and the resulting PTT‐O4 shows electron transport with a mobility of 0.022 cm 2 V −1 s −1 .